2014
DOI: 10.1007/s00213-014-3802-0
|View full text |Cite
|
Sign up to set email alerts
|

WY14643 produces anti-depressant-like effects in mice via the BDNF signaling pathway

Abstract: These data provide the first evidence that WY14643 exerts anti-depressant-like activity through promoting the BDNF signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 54 publications
(59 reference statements)
1
51
1
Order By: Relevance
“…In our conditions, CSDS failed to induce any modification in total Bdnf gene expression. This does not meet previous results that demonstrated a clear downregulation of total Bdnf gene in the hippocampus of social defeated mice, at both short and long term4754555657, although one study reported no change in the same conditions58. While Bdnf exon VI mRNA gene expression was also unchanged, Bdnf exon IV mRNA was significantly downregulated in CSDS stressed mice.…”
Section: Discussioncontrasting
confidence: 99%
“…In our conditions, CSDS failed to induce any modification in total Bdnf gene expression. This does not meet previous results that demonstrated a clear downregulation of total Bdnf gene in the hippocampus of social defeated mice, at both short and long term4754555657, although one study reported no change in the same conditions58. While Bdnf exon VI mRNA gene expression was also unchanged, Bdnf exon IV mRNA was significantly downregulated in CSDS stressed mice.…”
Section: Discussioncontrasting
confidence: 99%
“…In this experiment, the ICR mice were given the choice to drink from two bottles in individual cages, one with 1% sucrose solution and the other with water [26]. All the ICR mice were acclimatized for 2 days to two-bottle choice conditions, and the position of two bottles was changed every 6 h to prevent possible effects of side preference in drinking behavior.…”
Section: Sucrose Preference Experimentsmentioning
confidence: 99%
“…For induction of CRS, mice were restrained for 6 h/day up to 28 consecutive days in well-ventilated 50-ml polystyrene tubes. The CSDS was performed daily for 20 days according to our previous studies [26]. In this experiment, the CD1 retired breeders were used as the aggressors.…”
Section: Preparation Of Cus Crs and Csds Modelsmentioning
confidence: 99%
“…Before experiments started, all the mice were housed 5 per cage for one week under standard conditions (free access to food and water; lights from 07 : 00 to 19:00; room temperature 24±1°C), as we previously described. [29][30][31][32] All the behavioral experiments were performed during the day. All the procedures involving mice were conducted in accordance with the National Institutes of Health Guide for Care and Use of Laboratory Animals and with the Euro- Morris Water Maze The Morris water maze was conducted as we previously did.…”
Section: Animalsmentioning
confidence: 99%
“…29,35) Western Blotting Analysis The Western blotting method was also performed as we previously did. [29][30][31][32] Quantitative Real-Time Reverse Transcription PCR (qRT-PCR) Dectection The miR-206-3p, miR-206-5p, and BDNF mRNA levels were determined using qRT-PCR method. 28,[36][37][38] For the detection of miR-206, total miRNAs were isolated from the hippocampus and cortex using the mirVana miRNA isolation kit (Ambion, CA, U.S.A.).…”
Section: Animalsmentioning
confidence: 99%